PENINGKATAN KESADARAN KETAHANAN PANGAN MELALUI TALKSHOW ‘RAGAM INSPIRASI’ DALAM RANGKA HARI PANGAN NASIONAL - Usman, Usman (Media Literasi Indonesia, 2026)
Food security is a strategic issue that requires strengthening at the household level as the smallest unit within the food system. This community service activity aimed to enhance family-based food security awareness in commemoration of National Food Day through the “Ragam Inspirasi” talk show broadcast on Radio Peduli Kota Parepare. The program was conducted on September 18, 2025, and aired live via radio and Facebook to broaden audience reach. An educative-participatory approach was employed through an interactive dialogue between the speaker and the moderator, followed by a question-and-answer session with listeners. The topics covered included the concept of food security, its four pillars, the role of families in managing household food consumption, and the importance of local food diversification and balanced nutrition. The results indicated increased public literacy and awareness, as reflected in active participation and practical questions regarding household food management. Radio-based education proved to be an effective medium for reaching a broad audience and encouraging reflection on the crucial role of families in maintaining food stability. This activity contributes to strengthening local food security and supports sustainable development efforts at the community level.